Tectorigenin inhibits Caco-2 human colon cells via NF-κB pathway suppression (Bangladesh Journal of Pharmacology, 2015)
Effective immunomodulator and pro-inflammatory cytokine, Tumor necrosis factor-α (TNF-α) are considered to be responsible for connecting autoimmune pathological process and contagious diseases. TNF-α stimulates the C-X-C motif chemokine 10 (CXCL10) expression that is participated in migration of tumor, metastasis, and invasion. Tectorigenin, an o-methylated isoflavone, is present as a major portion in the Iris tectorum rhizomes. In this study, we investigated the tectorigenin effects as an anticancer drug. The obtained results showed that tectorigenin hinders the invasion of human colon cancer cells (Caco-2). We used reverse transcription PCR, q-PCR and enzyme linked immunosorbent assays to test whether the tectorigenin is involved in the inhibition of TNF-α induced CXCL-10 expression in the Caco-2 cell lines. Further, we tested TNF-α induced NF-κB activity using the tectorigenin. Collective results showed that tectorigenin inhibits the CXCL10 production by using TNF-α via NF-κB inhibition.